Electroencephalogram of Healthy Horses During Inhaled Anesthesia. (16th September 2015) - Williams, D.C.; Aleman, M.R.; Brosnan, R.J.; Fletcher, D.J.; Holliday, T.A.; Tharp, B.; Kass, P.H.; Steffey, E.P.; LeCouteur, R.A.
Abstract : Background: Previous study of the diagnostic validity of electroencephalography (EEG) to detect abnormalities in equine cerebral cortical function relied on the administration of various drugs for sedation, induction, and maintenance of general anesthesia but used identical criteria to interpret recordings. Objectives: To determine the effects of 2 inhalation anesthetics on the EEG of healthy horses. Animals: Six healthy horses. Methods: Prospective study. After the sole administration of one of either isoflurane or halothane at 1.2, 1.4, and 1.6 times the minimum alveolar concentration, EEG was recorded during controlled ventilation, spontaneous ventilation, and nerve stimulation. Results: Burst suppression was observed with isoflurane, along with EEG events that resembled epileptiform discharges. Halothane results were variable between horses, with epileptiform‐like discharges and bursts of theta, alpha, and beta recorded intermittently. One horse died and 2 were euthanized as the result of anesthesia‐related complications. Conclusions and Clinical Importance: The results of this study indicate that the effects of halothane and isoflurane on EEG activity in the normal horse can be quite variable, even when used in the absence of other drugs. It is recommended that equine EEG be performed without the use of these inhalation anesthetics and that general anesthesia be induced and maintained by other contemporary means.